Analysis of the Nature of Science on the Thematic Book of Elementary School Fifth Grade Heat and Its Displacement - Masitoh, Siti; Sa'ud, Udin Syaefudin; Ulfah, Sri Wahyuni (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Learning science must make the nature of science a guide. Pouring the content of the nature of science is not only the teacher's responsibility in learning, but also the nature of science must be included in the textbooks. There are three aspects/components of the nature of science that must fit in book's text readers, namely: (1) Products; (2) Process; and (3) Attitude. This research method uses descriptive research with content analysis. With the object of study, the thematic textbook document for the 2013 Class V Curriculum Integrated, Theme 6 is Heat and Its Transfer. The results showed that the nature of science was very well contained in the textbook, with a percentage of 100% on the aspects/components of Products and Processes and 55.5% on the parts elements factors characteristics/components of Attitude.